Rehabilitation of Maxillary Defect Using Zygomatic Implant Retained Obturator - Mounika Ayinala; Gautam Shetty (Case Reports in Dentistry)
Tumors involving the hard palate, maxillary sinus, or nasal cavity require maxillectomy based on the extent of the lesion. Lack of these boundaries affects the speech, esthetics, and masticatory function. Prosthetic rehabilitation of these defects can be done utilizing zygomatic implants. This present case describes the use of a zygomatic implant to retain a maxillary obturator in a 22-year-old male patient following partial maxillectomy (Brown’s Class 2b) due to odontogenic myxoma. A surgical obturator was secured in position subsequent to the implant placement. Following the healing period, an interim obturator using heat cure acrylic was fabricated. Mechanical retention for the definitive obturator was obtained through the ball attachment suspended from the multiunit abutment of the zygomatic implant. The case was followed up closely for a year to evaluate the function of the prosthesis. The prosthetic rehabilitation not only promoted esthetics and function but also improved the patient’s quality of life.